Mapping gender preferences for tree and shrub forages - Carsan, S.; Karanja E; Bourne, M.; Muchugi A; Franzel, Steven; Jamnadass, Ramni H. (World Agroforestry Centre, 2014)
The book is structured to cover a range of gender issues in various forest, trees and agroforest management areas from tree species identification to landuse decision-making. Participatory research tools are featured such as ranking, mapping, modeling, participatory GIS; and other tools that can aid in looking at gender issues, roles and preferences primarily but not limited to agroforestry research and development.